Device Therapies Among Patients Receiving Primary Prevention Implantable Cardioverter‐Defibrillators in the Cardiovascular Research Network. Issue 7 (26th March 2018) - Greenlee, Robert T.; Go, Alan S.; Peterson, Pamela N.; Cassidy‐Bushrow, Andrea E.; Gaber, Charles; Garcia‐Montilla, Romel; Glenn, Karen A.; Gupta, Nigel; Gurwitz, Jerry H.; Hammill, Stephen C.; Hayes, John J.; Kadish, Alan; et al.
Abstract : Background: Primary prevention implantable cardioverter‐defibrillators (ICDs) reduce mortality in selected patients with left ventricular systolic dysfunction by delivering therapies (antitachycardia pacing or shocks) to terminate potentially lethal arrhythmias; inappropriate therapies also occur. We assessed device therapies among adults receiving primary prevention ICDs in 7 healthcare systems. Methods and Results: We linked medical record data, adjudicated device therapies, and the National Cardiovascular Data Registry ICD Registry. Survival analysis evaluated therapy probability and predictors after ICD implant from 2006 to 2009, with attention to Centers for Medicare and Medicaid Services Coverage With Evidence Development subgroups: left ventricular ejection fraction, 31% to 35%; nonischemic cardiomyopathy <9 months' duration; and New York Heart Association class IV heart failure with cardiac resynchronization therapy defibrillator. Among 2540 patients, 35% were <65 years old, 26% were women, and 59% were white. During 27 (median) months, 738 (29%) received ≥1 therapy. Three‐year therapy risk was 36% (appropriate, 24%; inappropriate, 12%). Appropriate therapy was more common in men (adjusted hazard ratio [HR], 1.84; 95% confidence interval [CI], 1.43–2.35). Inappropriate therapy was more common in patients with atrial fibrillation (adjusted HR, 2.20; 95% CI, 1.68–2.87), but less common among patients ≥65 years old versus younger (adjusted HR, 0.72; 95% CI, 0.54–0.95) and in recent implants (eg, in 2009 versus 2006; adjusted HR, 0.66; 95% CI, 0.46–0.95). In Centers for Medicare and Medicaid Services Coverage With Evidence Development analysis, inappropriate therapy was less common with cardiac resynchronization therapy defibrillator versus single chamber (adjusted HR, 0.55; 95% CI, 0.36–0.84); therapy risk did not otherwise differ for Centers for Medicare and Medicaid Services Coverage With Evidence Development subgroups. Conclusions: In this community cohort of primary prevention patients receiving ICD, therapy delivery varied across demographic and clinical characteristics, but did not differ meaningfully for Centers for Medicare and Medicaid Services Coverage With Evidence Development subgroups.